Comparison of Medpor Coated Tear Drainage Tube versus Silicon Tear Drainage Tube in Conjunctivodacryocystorhinostomy: Problems and Solutions - Selam Yekta Sendul; Halil Huseyin Cagatay; Burcu Dirim; Mehmet Demir; Ali Atakhan Yıldız; Zeynep Acar; Sonmez Cinar; Dilek Guven (The Scientific World Journal)
Purpose. This study aims at comparing two different types of drainage tubes in conjunctivodacryocystorhinostomy, which are used for upper lacrimal system obstruction or damage, with respect to their respective postoperative problems and solutions. Methods. Nineteen eyes of 17 patients who underwent conjunctivodacryocystorhinostomy (CDCR) or conjunctivorhinostomy (CR) surgery with a Medpor coated tear drainage tube or silicon tube placement between October, 2010, and February, 2014, were included in this retrospective comparative study. Results. In the initial surgery, Medpor coated tear drainage tubes were used in 11 eyes by CDCR, whereas silicon tear drainage tubes were implanted into 2 eyes by CR and 6 eyes by CDCR. In group 1, proximal and distal obstructions developed postoperatively in 4 eyes, while 1 eye showed tube malposition and 3 eyes developed luminal obstruction by debris 3 times. In group 2, tube extrusion developed in 4 eyes, whereas tube malposition developed in 6 eyes and luminal obstruction by debris developed in 6 eyes at different times, for a total of 20 times. Conclusions. In our study, the most significant complication we observed in the use of silicon tear drainage tubes was tube extrusion,whereas the leading complication related to the use of Medpor coated tear drainage tubes was tube obstruction.